Genetically modified (GM) late blight-resistant potato and consumer attitudes before and after a field visit - Bubolz, J.; Sleboda, P.; Lehrman, A.; Hansson, S.O.; Johan Lagerkvist, C.; Andersson, B.; Lenman, M.; Resjö, S.; Ghislain, M.; Zahid, M.A.; Kieu, N.P.; Andreasson, E. (Informa UK Limited, 2022)
Late blight, caused by Phytophthora infestans, is the most devastating disease in potato production. Here, we show full late blight resistance in a location with a genetically diverse pathogen population with the use of GM potato stacked with three resistance (R) genes over three seasons. In addition, using this field trials, we demonstrate that in-the-field intervention among consumers led to change for more favorable attitude generally toward GM crops.